QUALITATIVE AND QUANTITATIVE ASSESSMENT OF OSTEOREGENERATION AT THE APPLICATION OF HYDROXYAPATITE IN SURGICAL PRACTICE - T. V. Druzhinina; Y. A. Kamenchuk; K. V. Trofimov; A. V. Rostovtsev; A. V. Zhulyabin; A. A. Isupov; A. V. Verevin (Acta Biomedica Scientifica, 2014)
The article shows the possibilities of multispiral computed tomography (MSCT) studies in the assessment of osteoregeneration of bone tissue after application of hydroxyapatite for filling of bone defects at different surgical operations. The comparative assessment of the rate of consolidation according to X-ray computed tomography (CT) in patients with bone fractures treated with the use of hydroxyapatite and without it is presented in the article. We studied 17 people (10 males and 7 females; average age - 39,3 ± 12,4 years). Revision arthroscopic plasty of anterior cruciate ligament of knee (n = 7 (58,3 %)), hydroxyapatite plasty of defect of bone tissue at the osteosynthesis of long bone fractures by metal constructions (n = 5 (41,6 %)) were realized. In 7 (58,3 %) cases the operation was performed with use of hydroxyapatite and in 5 (41,6 %) cases the surgery of osteosynthesis was realized with use of titanium plates. The dynamics of consolidation was determined by X-ray CT in 1, 2 and 4 months after surgery. As a result we received significant difference on the results of studies that testified to the stimulating effect of hydroxyapatite in the process of consolidation of fractures.